Generational Differences in Faculty and Student Comfort With Technology Use. (July 2020) - Culp-Roche, Amanda; Hampton, Debra; Hensley, Angie; Wilson, Jessica; Thaxton-Wiggins, Amanda; Otts, Jo Ann; Fruh, Sharon; Moser, Debra K.
Background: Navigating through online education courses continues to be a struggle for some nursing students. At the same time, integrating technology into online courses can be difficult for nursing faculty. Purpose: The purpose of this study was to assess faculty technology integration practices, student attitudes about technology use, and generational differences related to faculty and student technology use. Methods: A descriptive cross-sectional survey design was used to obtain data for this study. Results: Integration of technology into online courses and student attitudes about technology use were not significantly different by generation. Faculty and students from the Baby Boomer and Generation X reported less comfort using technology and higher levels of anxiety using technology than did individuals from Generation Y. Conclusion: Significant generational variations were not noted in relation to technology integration into courses and overall student attitudes about technology in this study, but differences were noted in relation to comfort with use of technology and anxiety when using technology. Student learning outcomes and satisfaction with learning may be influenced by the student's comfort using technology and faculty's confidence in integrating and using technology to provide online instruction.